Multi-Modal Nano Particle Labeling of Neurons - Amirav, Lilac; Berlin, Shai; Olszakier, Shunit; Pahari, Sandip K.; Kahn, Itamar (Frontiers in Neuroscience, 2019)
The development of imaging methodologies for single cell measurements over extended timescales of up to weeks, in the intact animal, will depend on signal strength, stability, validity and specificity of labeling. Whereas light-microscopy can achieve these with genetically-encoded probes or dyes, this modality does not allow mesoscale imaging of entire intact tissues. Non-invasive imaging techniques, such as magnetic resonance imaging (MRI), outperform light microscopy in field of view and depth of imaging, but do not offer cellular resolution and specificity, suffer from low signal-to-noise ratio and, in some instances, low temporal resolution. In addition, the origins of the signals measured by MRI are either indirect to the process of interest or hard to validate. It is therefore highly warranted to find means to enhance MRI signals to allow increases in resolution and cellular-specificity. To this end, cell-selective bi-functional magneto-fluorescent contrast agents can provide an elegant solution. Fluorescence provides means for identification of labeled cells and particles’ location after MRI acquisition, and it can be used to facilitate the design of cell-selective labeling of defined targets. Here we briefly review recent available designs of magneto-fluorescent markers and elaborate on key differences between them with respect to durability and relevant cellular highlighting approaches. We further focus on the potential of intracellular labeling and basic functional sensing MRI, with assays that enable imaging cells at microscopic and mesoscopic scales. Finally, we illustrate the qualities and limitations of the available imaging markers and discuss prospects for in vivo neural imaging and large-scale brain mapping.